Short-term Results of Using Injectable Bone Cement Technique in the Treatment of Unstable Distal Radius Fractures - A Poramiri; A.R Saied; SH Elka; L Ranjbar (Journal of Kerman University of Medical Sciences, 2012)
Background & Aims: Treatment of osteoporotic distal radius fracture with metaphyseal defect is often complicated by secondary displacement, because of posterior cortex comminution. The aim of this study was to investigate functional outcomes and advantages of injection of bone cement in stabilizing and maintaining this fracture reduction. Methods: This prospective study was performed on 20 patients aged fifty years and older. After primary reduction and bone cement injection into metaphyseal void through minimal dorsal distal forearm incision, a short arm cast was applied for 3 weeks. Then the cast was removed and free use of the wrist was begun. Patients were assessed after 6 weeks, 3 months and 6 months in regard to active wrist range of motion, pain score, grip strength, DASH score, modified Mayo wrist score and standard radiographic parameters. Results: The patients included 3 men and 17 women with the mean age of 67 years old. According to the AO classification, there were seventeen type-A3 and three type-C2 distal radius fractures. At final follow up, the active range of motion of the injured side relative to uninjured side averaged 91% of flexion, 93% of extension, 91% of radial deviation, 93% of ulnar deviation, 98% of pronation and 99% of supination. Mean DASH score was 4.4. Grip strength was 90% of the uninjured side. According to the modified Mayo wrist score, there were fourteen excellent and six good results. Mean final radiographic parameters were 10° of volar angle, 24° of radial inclination, 10 mm of radial length, 1 mm of ulnar variance, and 0.3 mm of intraarticular gap. Each of median nerve hyposthesia due to compression before reduction, loss of reduction, soft tissue cement deposit and reflex sympathetic dystrophy, occurred in one patient. None of the patients had further complications. Conclusion: According to the results, injection of bone cement in osteoporotic unstable distal radius fracture can be considered a safe and effective treatment method; it causes clinical functional improvement and rapid rehabilitation with little complications.